Effects of endoscopy-related procedure time on musculoskeletal disorders in Japanese endoscopists: a cross-sectional study - Matsuzaki, Ippei; Ebara, Takeshi; Tsunemi, Mafu; Hatta, Yoshifumi; Yamamoto, Kojiro; Baba, Akemi; Hattori, Masashi; Nakamura, Masanao; Fujishiro, Mitsuhiro (Endoscopy International Open, 2021)
Background and study aims There has been little evidence assessing the prevalence of musculoskeletal disorders (MSDs) among endoscopists performing recent diagnostic and therapeutic endoscopic procedures requiring prolonged procedural times. We evaluated the prevalence and identified the risk factors for developing MSDs, focusing on procedural time. Methods An electronic survey of endoscopists (n = 213) employed at the Nagoya University Hospital and its affiliated hospitals was developed by a multidisciplinary group. Results Of the 110 endoscopists (51.6 %) who responded to the survey, eighty-seven endoscopists (79.1 %) had experienced endoscopy-related MSDs during the previous 1 year, and 49 endoscopists (44.5 %) had experienced these MSDs during the previous week. Nineteen endoscopists (17.3 %) reported absence from work due to severe MSDs. The most frequent sites of MSDs were neck, low back, and shoulders. Logistic regression analyses showed that longer upper endoscopic submucosal dissection ESD, (odds ratio: 5.7; 95 %CI: 1.3–25.0), lower ESD (odds ratio 4.9; 95 %CI: 1.1–22.0), and lower gastrointestinal treatment (odds ratio: 5.6; 95 %CI: 2.3–13.3) were significantly associated with the development of MSDs in the low back area. Moreover, longer lower ESD (odds ratio: 5.0; 95 % CI: 1.2–20.2) was a risk factor for symptoms in the left shoulder. Conclusion This study suggests a correlation between the volume of therapeutic endoscopic procedures including ESD and the risk of MSDs mainly low back area and left shoulder. Managing monthly total endoscopic time, in light of organizational ergonomics, could contribute to minimizing such risks of endoscopy-related MSDs.